Characterization of Insulin and Glucagon Genes and Their Producing Endocrine Cells From Pygmy Sperm Whale (Kogia breviceps) - Zhao, Liyuan; Wang, Likun; Aierken, Reyilamu; Wang, Wei; Wang, Xianyan; Li, Mingyu (Frontiers in Endocrinology, 2020)
Insulin and glucagon are hormones secreted by pancreatic β and α cells, respectively, which together regulate glucose homeostasis. Dysregulation of insulin or glucagon can result in loss of blood glucose control, characterized by hyperglycemia or hypoglycemia. To better understand the endocrine physiology of cetaceans, we cloned and characterized the insulin and glucagon genes from pygmy sperm whale (Kogia breviceps). We obtained the complete coding sequences of the preproinsulin and preproglucagon genes, which encodes the preproinsulin protein of 110 amino acid (aa) residues and encodes the preproglucagon protein of 179 aa residues, respectively. Sequence comparison and phylogenetic analyses demonstrate that protein structures were similar to other mammalian orthologs. Immunohistochemistry and immunofluorescence staining using insulin, glucagon, and somatostatin antibodies allowed analysis of pygmy sperm whale islet distribution, architecture, and composition. Our results showed the pygmy sperm whale islet was irregularly shaped and randomly distributed throughout the pancreas. The architecture of α, β, and δ cells of the pygmy sperm whale was similar to that of artiodactyls species. This is the first report about insulin and glucagon genes in cetaceans, which provides new information about the structural conservation of the insulin and glucagon genes. Furthermore, offers novel information on the properties of endocrine cells in cetacean for further studies.